2018
DOI: 10.3390/e20090668
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration and Viscous Dissipation Effects on Entropy Generation in Hybrid Nanofluid Flow over a Nonlinear Radially Stretching Disk

Abstract: The present research work explores the effects of suction/injection and viscous dissipation on entropy generation in the boundary layer flow of a hybrid nanofluid (Cu–Al2O3–H2O) over a nonlinear radially stretching porous disk. The energy dissipation function is added in the energy equation in order to incorporate the effects of viscous dissipation. The Tiwari and Das model is used in this work. The flow, heat transfer, and entropy generation analysis have been performed using a modified form of the Maxwell Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 33 publications
(40 reference statements)
6
47
0
Order By: Relevance
“…From Table 2, it can be observed that when h n f φ is increased, it leads to an increase in density and viscosity, and a decrease in velocity. The same trend for h n f φ was reported by Farooq et al [21]. It must be remembered that this effect is true when the temperature of the fluid is between 0 °C and 180 °C.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…From Table 2, it can be observed that when h n f φ is increased, it leads to an increase in density and viscosity, and a decrease in velocity. The same trend for h n f φ was reported by Farooq et al [21]. It must be remembered that this effect is true when the temperature of the fluid is between 0 °C and 180 °C.…”
Section: Resultssupporting
confidence: 85%
“…It is worth mentioning that by making φ Ag = 0 or φ TiO 2 = 0, the modified model can be successfully reduced to nanofluid expressions. The numerical values of the thermophysical properties of the nanoparticles and base fluid are presented in Table 1, and the expression can be found in Table 2 [21,43,44]. Table 2.…”
Section: Thermophysical Properties Of Hybrid Nanofluidmentioning
confidence: 99%
See 1 more Smart Citation
“…From an engineering perspective, the concept of entropy generation analysis can be therefore useful in order to characterize the evolution of thermal processes and also as a design tool in order to avoid the imminent loss of available mechanical power in thermo-fluid systems [13,14], likewise for the conceptual design of jet impingement cooling applications. Various investigations on entropy generation have been reported in the literature for different configurations and physical processes using numerical and analytical approaches, e.g., [11,[15][16][17][18][19][20][21][22]. A detailed description of the theoretical background of entropy generation analysis can be found in [23,24] and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Afridi et al [28] compared the flow and heat transfer in two different base fluids and two different hybrid fluid flows by utilizing the three-stage Lobatto IIIA formula. Farooq et al [29] reported the transpiration effects on entropy generation in hybrid nanofluid flow with energy dissipation. Some recent innovative research on hybrid nanofluid is mentioned in [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%